The fate of ectomycorrhizal fungi associated with Pinus radiata seedlings in the nursery - Walbert, K.; Ramsfield, T.D.; Dick, M.A.; Jones, E.E.; Ridgway, H.J. (New Zealand Plant Protection, 2008)
Ectomycorrhizal (ECM) fungi dramatically enhance the growth of the plantation species Pinus radiata and facilitate the establishment of nursery seedlings following outplanting This study investigated ECM species colonising P radiata seedlings in the nursery and their fate in the first year of outplanting Naturally occurring ECM communities of P radiata seedlings in the Te Ngae Nursery Rotorua were investigated and these seedlings were assessed following outplanting in Kaingaroa Forest Observations of the ECM communities were made eight times during the first year of the seedlings being in the plantation forest In addition the ECM communities of 1 2 and 8 year old P radiata plantation stands were also analysed It was found that nursery ECM survived the first year of outplanting The first nonnursery ECM Pezizales sp occurred 6 months after outplanting at Kaingaroa but these were in minor abundance Rhizopogon rubescens was the most persistent and dominant nursery ECM species Overall nursery ECM survived for 2 years following outplanting but were completely replaced by 7 years